Mercury Content on Mangrove Roots and Telescopium telescopium in Kao Bay, North Halmahera - Moh. Fauzan Jafar Moh. Fauzan Jafar; Reni Tyas Asrining Pertiwi (Masyarakat Moluska Indonesia, 2021)
The process of extracting gold using mercury (Hg) carried out by Nusa Halmahera Minerals industries (PT. NHM) as well as by the community of illegal gold mining or gold mining without a permit (PETI) that occurs in the mining area of ​​Halmahera Island can have a negative impact on the aquatic environment. This study aims to determine the mercury absorption in mangrove roots of Rhizopora sp and Telescopium telescopium at two different stations. Sampling of mangrove roots was repeated 3 times for each station. Differences in the accumulation of heavy metals Hg in the roots of Rhizophora sp were analyzed using the T-test. The study showed that the concentration of mercury in the roots of Rhizophora sp ranged from 0.016 – 0.026 mg/kg and there were differences in root absorption between Rhizopora sp at station 1 of the Tabobo River mangrove near the PETI disposal and station 2 at the mining industry waste disposal. The concentration of mercury in Telescopium telescopium ranged from 0.08 - 0.15 mg/kg. It is indicates that Telescopium telescopium in Kao Teluk has been contaminated with mercury but is still below the threshold of the quality standard that has been set.